2014
DOI: 10.1111/pde.12436
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Serum 25‐Hydroxyvitamin D and Virulence Genes of Staphylococcus aureus Isolates Colonizing Children with Atopic Dermatitis

Abstract: The skin of children with atopic dermatitis (AD) is colonized with Staphylococcus aureus more frequently than that of their peers. We investigated the prevalence of skin and nares colonization by S. aureus in children with AD, the virulence genes of the isolates, and their association with allergy, AD severity, and serum vitamin D (25(OH)D). This was an observational, cross-sectional study in a sample of children diagnosed with AD in two settings in Spain. The samples were collected in 2012. Swabs from affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
0
14
0
6
Order By: Relevance
“…Because AD can be worsened by an overlying bacterial infection, an observational, cross-sectional study investigated the relationship between levels of vitamin D and S. aureus virulence factors [22]. Several virulence factors, including tsst-1, eta, cna, aur, and sec, were associated with lower 25[OH]D levels, indicating that vitamin D deficiency can be associated with more virulent overlying S. aureus infections in patients with AD.…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…Because AD can be worsened by an overlying bacterial infection, an observational, cross-sectional study investigated the relationship between levels of vitamin D and S. aureus virulence factors [22]. Several virulence factors, including tsst-1, eta, cna, aur, and sec, were associated with lower 25[OH]D levels, indicating that vitamin D deficiency can be associated with more virulent overlying S. aureus infections in patients with AD.…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…AD patients are susceptible to the skin colonization and infection by S. aureus , which through the production of exotoxins with supra-antigenic properties aggravates the disease. Gilaberte et al [145] have observed a significant association between low serum vitamin D levels and certain virulence genes of S. aureus in isolates of AD children suggesting some role of vitamin D deficiency in S. aureus colonization. Thus, vitamin D supplementation could be promising in reducing the cutaneous S. aureus burden in AD patients.…”
Section: Role Of Vitamin D In Certain Inflammatory Skin Diseasesmentioning
confidence: 99%
“…hastalarda S.aureus kolonizasyonu olanlarda serum total IgE düzeyleri daha yüksek ölçülmüştür (24). Bir başka çalışmada ortalama serum total IgE düzeyi nazal bakteriyel kolonizasyonu olanlarda yüksek bulunmuştur ancak fark anlamlı değildir (20). Çalışmamızda sadece nazal S.aureus kolonizasyonu olanlarda serum total IgE düzeyi yüksek bulunmuştur.…”
Section: Bulgular çAlışma Gruplarının Klinik öZellikleriunclassified
“…Fakat sonuçlarımızın aksine, Gilaberte ve ark. (20) atopik olanlarda deride bakteriyel S.aureus kolonizasyonun daha yüksek olduğunu gösterdi. Önceki çalışmadan farklı olarak biz atopiyi DPT yöntemi ile değerlendirdik.…”
Section: Bulgular çAlışma Gruplarının Klinik öZellikleriunclassified
See 1 more Smart Citation